Factors that influence carreer choice in Colombia: industrial engineering as case study (2019)
This paper analyzes the influence of the offer expansion on technical and technological careers, salary expectations, and college reputation in the decision to choose a professional career. The study focused on the Industrial Engineering program using secondary information on salaries, population, and number of enrollees. The analysis period covers the years 2007-2015. The main conclusions show that although there are no significant differences in the salaries of recent graduates of industrial engineering, those from more expensive universities tend to earn salaries significantly higher over time. Large investments, necessary to complete professional studies, make return rates much lower than for the rest of universities.